Implications of Allowing & Removing Short Selling: Empirical Evidence from Malaysia Stock Market - Mohamed Ziauddin, Syed Ebrahim (2010)
Short selling regulations have been changed few times in a decade in the Malaysian Stock Exchange market. First the government removed the restrictions placed on short selling, and then due to the Asian Financial Crisis the government suspended short selling in order to avoid speculations in the market. Then again after almost a decade, the government reintroduced short selling in the market. These events taking place provides an opportunity to study the effect these events have on market behaviour such as market skewness, market volatility, market liquidity and market return. Thirty stocks were selected from Kuala Lumpur Stock Exchange (KLSE) on the basis that they were allowed for short selling twice during 1996 and 2007. This data is then analysed with dummy variables such as SS feasibility (short selling feasibility) and Crisis (financial crisis) to study the impact it has on the market. For the first time frame, the findings suggest that the removal of short selling restrictions has no effect on the market skewness and market liquidity. However the introduction of short selling during this period reduces the volatility in the market. The market return was measured using cumulative abnormal returns and the returns increased as a result of the removal of short selling restriction and the cumulative abnormal returns decreased when short selling restriction were placed again. During the second time frame, the removal of short selling restriction had no effect on the skewness. However volatility and liquidity increased as a result of lifting the restrictions. The cumulative abnormal returns increased as a result of the removal of short selling. The results from both periods differ among them because both this time frame took place during different financial crisis, hence there are possibilities that not only the information of short selling regulations but also the impact of financial crisis surrounding the market affecting the market. In this paper it is also tested if short selling is able to reduce the impact of financial crisis and the findings suggest that the removal of the restriction may reduce the impact financial crisis has on market liquidity and no evidence was found if short selling reduces market volatility, skewness and return.